Pengaruh Social Media Marketing, Influencer Marketing Dan Brand Image Terhadap Keputusan Pembelian Pada Aplikasi Tiktok - Imam Maulana Hidayatullah; Muhammad Mansur; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine whether there is between social media marketing, influencer marketing and brand image on purchasing decisions on the TikTok application. The type of research used in this research is descriptive quantitative research. The data processed in this study is the result of distributing questionnaires to students of the Faculty of Economics and Business at the Malang Islamic University who have made transactions on the TikTok application, totaling 95 respondents. The sampling method is non-probability sampling and the technique used in collecting respondents is snowball sampling. The analysis technique used in this study is multiple linear regression. The results showed that the results of the t (partial) test of social media marketing had an effect on purchasing decisions as indicated by a t value of 2.027, influencer marketing had no effect on purchasing decisions as indicated by a t value of 1.601, and brand image involvement had an effect on purchasing decisions as indicated with a t value of 2.916 while the results of the F test show that the calculated F is 0.000 which is less than 0.05. This means that social media marketing, influencer marketing and brand image together influence purchasing decisions on the TikTok application. Based on the calculation of the coefficient of determination, it shows that the Adjusted R Square is 37% and the remaining 63% can be explained by other variables that are not in this study. Keywords : Social Media Marketing, Influencer Marketing, Brand Image and Purchasing Decisions